Storage of pasteurized milk in clear PET bottles combined with light exposure on a retail display case: A possible strategy to define the shelf life and support a recyclable packaging. (1st November 2020) - Limbo, Sara; Pellegrino, Luisa; D'Incecco, Paolo; Gobbi, Serena; Rosi, Veronica; Fracassetti, Daniela
Highlights: Effects of lighting on pasteurized milk in clear PET bottles were studied during shelf storage. Major light-induced changes involved flavins, volatiles and sensory properties. Shelf life of pasteurized milk was defined considering its overall characteristics. Estimated shelf life was longer than that assigned by the manufacturer. Light exposure management by retailers is crucial to preserve bottled milk quality. Abstract: The stability of whole pasteurized milk packaged in clear PET bottles was studied throughout 13-days storage in the dark, but including, at specific times, light exposure of 6, 12 or 18 h to simulate conditions potentially occurring in refrigerated display counters. The aim was to investigate the effects of light exposure when overlapping the unavoidable endogenous modifications in pasteurized milk during storage. Dissolved oxygen, riboflavin and other flavins, proteolysis products, volatile compounds, and sensory characteristics were evaluated. Besides the expected progress of proteolysis occurring during storage, light negatively affected milk flavour especially after longer exposure times. The development of "mushroom" flavor related to the increase of volatile 2, 3 octanedione was the most characterizing modification. Gathered data were considered in view of providing the background knowledge for the control of light exposure conditions on a retail display, thus supporting the shelf life extension of pasteurized milk in a fully recyclable packaging.